Nitroxyl protects H9C2 cells from H/R-induced damage and inhibits autophagy via PI3K/Akt/mTOR pathway - Li Li; Zhixin Wang; Yaxuan Lyu; Yanqing Guo (PLoS ONE, 2025)
Background Myocardial ischemia-reperfusion injury (MIRI) is an important complication in the treatment of heart failure, and its treatment has not made satisfactory progress. Nitroxyl (HNO) showed protective effects on the heart failure, however, the effect and underlying mechanism of HNO on MIRI remain largely unclear. Methods MIRI model in this study was established to induce H9C2 cell injury through hypoxia/reoxygenation (H/R) in vitro. The cell viability was assessed by cell counting kit-8 assay. The effect of HNO on the apoptosis was detected by flow cytometry. DCFH-DA fluorescent probe method was applied to detect the level of intracellular reactive oxygen species (ROS). The morphology of mitochondria and autophagosomes were observed by transmission electron microscopy. Apoptosis, autophagy and PI3K/Akt/mTOR pathway-related proteins were detected by western blot. Results The viability of H9C2 cells was significantly increased in the HNO group. HNO inhibited apoptosis and regulated expressions of key apoptotic protein, including Bax and Bcl-2. HNO reduced ROS levels and alleviated H/R-induced mitochondrial damage. HNO also inhibited autophagy and regulated expressions of key autophagy-related molecules, including LC3II, p62 and Beclin1. Further experiments demonstrated that the effects of HNO were mediated through upregulation of PI3K/Akt/mTOR pathway. Rapamycin reversed the inhibition of HNO on H/R-induced autophagy in H9C2 cells, which abrogated the protective effect of HNO. Conclusion This study provided the first evidence that HNO protected H/R-induced cardiomyocytes through inhibiting autophagy via the activation PI3K/Akt/mTOR pathway.